"I did whatever they wanted me to do": a qualitative secondary analysis using reproductive justice to explore sexual violence among justice-involved Latina mothers - A. D. Crawford; K. McGlothen-Bell; L. M. Cleveland (BMC, 2022)
Abstract Background One in three women experience sexual violence during their lifetime; however, little is known about this phenomenon with respect to justice-involved Latina mothers. Using the reproductive justice framework as a theoretical lens, we examined sexual violence in Latina mothers who had experienced incarceration and were thus involved in the justice system. Methods This was a secondary analysis of a qualitative data set. The reproductive justice framework provided a theoretical lens for examining the women's rights to bodily autonomy, to have or not have children, and to live in safe, sustainable environments given the intersection of incarceration and sexual violence. Results Women (N = 12) recounted their experiences of sexual violence after having been incarcerated. Incarceration and resulting sexual violence led to discrimination, limited bodily autonomy, sexual exploitation, substance use, depression, anxiety, re-traumatization, recidivism, underreporting of violence, underutilization of healthcare resources, strained relationships, family separation, and unsafe environments. Conclusions More research is needed to understand the social, economic, and political contexts that perpetuate sexual violence among justice-involved women. Universal healthcare, participatory research, changing cultural mindsets, decriminalization of sex work, and more comprehensive tracking and prosecution of sexual predators may be key to ending sexual violence in justice-involved mothers.